Kwotowanie produkcji mleka w latach 2004/2005 i 2005/2006 na Dolnym Śląsku - Mierzwa, Danuta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The article presents Lower Silesia as compared to other provinces with regard to the purchase and processing of milk. Despite the conditions conducive to milk cattle breeding it can be noted that Lower Silesia is low on the ranking list. The processing of milk has collapsed, whereas small suppliers ceased to produce. It can be noticed that the system of limited milk amounts has brought about the specialization of the regions. The top places on the ranking list are taken up by the following provinces: podlaskie, mazowieckie, and wielkopolskie. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 216-222